Infertility and non-traditional families - Roache, Rebecca (Journal of medical ethics, 2016)
This issue's Feature Article and accompanying commentaries focus on the issue of uterine transplantation (UTx). Stephen Wilkinson and Nicola Jane Williams consider, in the Feature Article, whether there is any good reason why publicly funded healthcare systems such as the UK's National Health Service (NHS) should not fund UTx in the event that it becomes sufficiently safe and efficacious. They argue that public funding for UTx should not be denied on the ground that creating more people would contribute to climate change problems, nor on the ground that infertility might be better viewed as a social problem rather than a disease. They then question whether systems like the NHS might decline to fund UTx on the ground that there exist sufficiently good, cheaper alternatives to the problem of absolute uterine factor infertility (AUFI), such as adoption and surrogacy. Both of these alternative options offer the possibility of ‘social parenthood’ (rearing children), which the authors note is the most powerful reason for the state to fund fertility treatment. However, neither of these alternatives is quite satisfactory. Prospective parents typically do not merely want social parenthood, they also want genetic and gestational parenthood (parenting a child to whom one is genetically related, and whom one parent has gestated). Adoption offers neither genetic nor gestational parenthood, and surrogacy offers at most only genetic parenthood. Wilkinson and Williams argue that while genetic and gestational parenthood are not the strongest reasons for the state to fund fertility treatment, neither are they so insignificant that they can plausibly regarded as mere ‘frills’ or ‘optional extras’. The authors concede that surrogacy might become a sufficiently good alternative to safe and efficacious UTx if the law surrounding it were reformed; until then, the case for refusing state funding for UTx is weak.Wilkinson and Williams's article is accompanied …